Persuasive Dialogue through the Prism of Pragmalinguistic (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
Linguistic strategies play a crucial role in persuasive communication, influencing the effectiveness of messages and interactions. Indirect Speech Acts, for example, allow speakers to convey their intentions subtly, often resulting in a more polite and less confrontational approach. Politeness strategies, such as the use of mitigating language or positive politeness, can help speakers to maintain harmony and avoid potential face-threatening acts. Contextual adaptation involves adjusting language and communication style to suit the specific social, cultural, and situational context, thereby enhancing the persuasiveness of the message. Persuasive dialogue involves the strategic use of language and discourse to influence the beliefs, attitudes, and behaviors of others. Pragmalinguistics explores the relationship between language and context, shedding light on how linguistic choices impact persuasive communication.